2007
DOI: 10.1111/j.1365-2834.2007.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer-supported telephone nurse triage: an evaluation of medical quality and costs

Abstract: The telephone nurse triage model showed adequate guidance for the patients concerning level of care and released resources for the benefit of both patients and the health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(112 citation statements)
references
References 34 publications
4
106
0
2
Order By: Relevance
“…NTLs are also beneficial in that they reduce strain on the HCS, offer high levels of patient satisfaction, and serve as a safe, efficient, and cost-effective method of information dissemination. [19][20][21][22][23][24] Benefits can also be seen in reduced travel costs, reduced time away from school/work, and reduced childcare expenses. 17 …”
Section: Discussionmentioning
confidence: 99%
“…NTLs are also beneficial in that they reduce strain on the HCS, offer high levels of patient satisfaction, and serve as a safe, efficient, and cost-effective method of information dissemination. [19][20][21][22][23][24] Benefits can also be seen in reduced travel costs, reduced time away from school/work, and reduced childcare expenses. 17 …”
Section: Discussionmentioning
confidence: 99%
“…72 57 also reported on appropriateness and 11 of the studies identified here were included in the review by Blank et al 73,[75][76][77][80][81][82]84,88,90 This review identified that triage decisions rated as appropriate varied between 44% and 98%. However, many different definitions of appropriateness were used, which leads to difficulty when trying to compare results.…”
Section: Service Impactsmentioning
confidence: 99%
“…93,94 Costs Nine studies reported costs or cost savings. 75,79,86,101,[108][109][110][111][112]126 The most common method of calculating and reporting costs was to report costs saved from callers' change in subsequent health-care-seeking behaviour as a result of the call. 75,79,108,110 These were not consistently reported and were reported as average per patient savings, cost savings per call recommendation type, annual net savings and overall reduction, making comparison difficult.…”
Section: Safetymentioning
confidence: 99%
“…Services provided at these call centres can in this way prevent unnecessary medical visits and result in financial savings for healthcare systems. They also have the potential to improve self-care for the public [5,8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…Nurse-led telephone triage has been introduced in many Western countries, for example Holland, Australia, UK and Sweden [2][3][4][5] . Competent telenurses at well-organised call centres estimate the urgency of callers' health problems, recommend the best course of action for each individual caller, and try to steer the callers to optimal care levels [5][6][7] . Services provided at these call centres can in this way prevent unnecessary medical visits and result in financial savings for healthcare systems.…”
Section: Introductionmentioning
confidence: 99%